Peran Model Kepemimpinan Spiritual Dalam Mendukung Program Pengentasan Kemiskinan (Studi Pada Baitul Mal Wat Tamwil) - Sri Padmantyo; Zulfa Irawati; Sri Murwanti; Ahmad Shilbi Sulton; Muhammad Sholahuddin (Benefit: Jurnal Manajemen dan Bisnis, 2020)
Some research shows that microfinance institutions can help them improve their standard of living. In organizational behavior theory, a leader really determines the success of a program. However, no leadership model has been found in Islamic microfinance institutions that play a role in the success of the program to help increase the lives of customers who are on the verge of poverty. Research in the first year has concluded that vision, hope / faith, altruistic love, meaning / calling, membership, commitment and job satisfaction have a significant positive effect on spiritual leadership. The implication of the results of this study is that the management of human resources (HR) and company management along with all policies directly related to HR aspects are better based on the application of spiritual leadership by managers. However, empirical evidence has not yet been found that the role of spiritual leadership on the successful management of poverty alleviation programs in Islamic microfinance institutions. The second year of research aims to find empirical evidence with a qualitative approach. data with content analysis approach.